Peripheral iridectomy procedure in angle closure glaucoma - Masitha Dewi Sari (Majalah Kedokteran Nusantara The Journal Of Medical School, 2014)
Objective : To report angle closure glaucoma cases treated by peripheral iridectomy.Methods : A 42 year-old woman come to Ophthalmology Departement,Adam Malik Hospital with chief complaint of pain in the right eye for 1 week. Visual acuity in the right eye no light perception and eye pressure 21 mmHg. On examination found sklerektasis, shallow anterior chamber, posterior synechial, slightly cloudy cornea and the lens . Patient is diagnosed absolute angle closure glaucoma and treated by peripheral iridectomy procedure.Result : Pain and Intraocular pressure were reduced after sugical iridectomy.Conclusion : In Absolute glaucoma cases without complain does not require any treatment. The goal of surgical procedure is important to minimizing pain.